Treatment Evaluation of Concomitant Femoral Neck and Shaft Fractures - Zubair Javaid, Obaid Ur Rehman,Islam Uddin,Syed Furqan, (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the results of fixation of fracture neck of femur associated with fracture shaft of femur, by reconstruction nail or lag screws with conventional nail system. Methods: In this descriptive study, 22 patients, with ipsilateral femoral neck and shaft fracture were included. Reconstruction nails were used in 16 cases and cancellous lag screws in 06 cases, where femur had been already fixed with k nail and interlocking nail. Results: Majority (90.9%) were male. Complex fracture of femoral shaft and neck was seen in 72.72%. In majority ( 81.81%) %) type II Gorden Fracture took place.Patients were mobilized on crutches on second day of surgery and were not allowed weight bearing till union of neck of femur. No case of avascular necrosis or non union of neck fracture was noted. Conclusion: Reduction of neck fracture is the key factor for good outcome. Patients with complex fractures requires minimally invasive techniques. There should be lesser soft tissue dissection to prevent complications. Where reconstruction nail is not possible two to three lag screws with good reduction of neck of femur has satisfactory results.